2020
DOI: 10.1007/s43450-020-00025-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Healing Potential of Myracrodruon urundeuva in Wounds Induced in Male Rats

Abstract: Myracrodruon urundeuva Allemão, Anacardiaceae, is popularly known as "aroeira-do-sertão". It is a common species in the state of Ceará and widely used for its anti-inflammatory, anti-ulcer, astringent, anti-allergic, and antidiarrheal activities and also in the treatment of skin wounds. The aim of this study was to evaluate the healing effect of the cream prepared with the decoction from the stem bark of a 7-year-old cultivated M. urundeuva in rats submitted to excisional wounds. Male Wistar rats were divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The chemical composition of the nanogels showed the compound class, such as terpenes, chalcone, tannin, and flavonoids. [12] Literature data also showed similar compositions for M. urundeuva extract with presence of tannin, flavonoids [19,[26][27][28] and chalcones named urundeuvin A, B and C [23,25,29] and L. sidoides essential oil with thymol and carvacrol as major components. [14,[30][31][32] After 7 days of treatment, the macroscopic and microscopic analysis of wound closure dynamics showed that NAA was not able to reduce the inflammatory typical responses.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…The chemical composition of the nanogels showed the compound class, such as terpenes, chalcone, tannin, and flavonoids. [12] Literature data also showed similar compositions for M. urundeuva extract with presence of tannin, flavonoids [19,[26][27][28] and chalcones named urundeuvin A, B and C [23,25,29] and L. sidoides essential oil with thymol and carvacrol as major components. [14,[30][31][32] After 7 days of treatment, the macroscopic and microscopic analysis of wound closure dynamics showed that NAA was not able to reduce the inflammatory typical responses.…”
Section: Discussionmentioning
confidence: 59%
“…In other study, the literature data was showed that the aqueous extract 10 % of "aroeira-dosertão" applied to wounds delayed the evolution of the initial phases of the cicatricial process, possibly related to its antiinflammatory effects. [19,26,41,43] In addition, the extract promoted an improvement in the collagen deposit at 14 days, reduced the bacterial concentration at the wound site and did not affect the dynamics of the healing process.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations